Towards sustainable production of renewable chemicals from lignin - Eshtaya, Majd (2016)
Environmental concerns have brought attention to the requirement for more efficient and renewable processes for chemicals production. Lignin is the second most abundant natural polymer, and might serve as a sustainable resource for manufacturing fuels and aromatic derivatives for the chemicals industry after being depolymerised. In this work, two main approaches were investigated with the aim of treatment of lignin with a mediator, 2,2’-azinobis(3-ethylbenthiazoline-6-sulfonic acid) diammonium salt (ABTS), in 1-ethyl-3-methylimidazolium ethyl sulfate, ([C2mim][C2SO4]). In the first approach, laccase from Trametes versicolor (LTV) was used to treat organosolv lignin, using [C2mim][C2SO4] as a co-solvent in the presence of ABTS. LTV was shown to possess catalytic activity for the degradation of organolsov lignin in systems containing ionic liquid and syringaldehyde was found to be a major product obtained from the process.